Pomen topnega receptorja za interlevkin-2 pri sepsi - Pokrajac, Tatjana (Zdravniški vestnik, 2001)
Background. The soluble interleukin-2 receptor (s-IL-2R) is a soluble cytokinereceptor which directly reflects the levels of the IL-2 receptor on lymphocytes T, which, along with the IL-2 itself, is important for the specific immune response. The aim of the study. We attempted to prove diagnostic and prognostic significance of s-IL-2R in sepsis cases. Patients and methods. In the period of three years we examined 64 healthy blood donors and subjects in systematic health examinations and examined 50 septic patientswith clinical and laboratory symptoms of sepsis treated in units for the intensive therapy of adults at the Clinic for Infectious Diseases and Febrile States at the Clinic Centre of Ljubljana. The assay for s-IL-2R was performed with a kit from Eurogenetic (Belgium). Results. We proved that the median concentration of s-IL-2R in septic patients with positive and negative blood culture are significantly higher than healthy subjects (p<0.05) and werealso significantly higher in the blood of dead patients than in the blood of survivors (p<0.05). The mean concentration of s-IL-2R did not differ in septic patients with positive blood culture from those with negative blood culture and did not differ for gram negative pathogenes from those for gram positive pathogens. Time dynamics showed the increase levels of s-IL-2R for the first 48 hours. Conclusions. s-IL-2R levels are elevated in adults with sepsis. Elevation of s-IL-2R are significantly associated with death.
Keywords: Diagnosis; diagnostika; infekcijske bolezni; Prognosis; Prognoza; receptorji; Receptorji, interlevkin-2; Receptors, interleukin-2; Sepsa; Sepsis